Competitive interactions modify the temperature dependence of damselfly growth rates. Issue 5 (1st May 2014) - Nilsson-Örtman, Viktor; Stoks, Robby; Johansson, Frank
Abstract : Individual growth rates and survival are major determinants of individual fitness, population size structure, and community dynamics. The relationships between growth rate, survival, and temperature may thus be important for predicting biological responses to climate change. Although it is well known that growth rates and survival are affected by competition and predation in addition to temperature, the combined effect of these factors on growth rates, survival, and size structure has rarely been investigated simultaneously in the same ecological system. To address this question, we conducted experiments on the larvae of two species of damselflies and determined the temperature dependence of growth rate, survival, and cohort size structure under three scenarios of increasing ecological complexity: no competition, intraspecific competition, and interspecific competition. In one species, the relationship between growth rate and temperature became steeper in the presence of competitors, whereas that of survival remained unchanged. In the other species, the relationship between growth rate and temperature was unaffected by competitive interactions, but survival was greatly reduced at high temperatures in the presence of interspecific competitors. The combined effect of competitive interactions and temperature on cohort size structure differed from the effects of these factors in isolation. Together, these findings suggest that it will be challenging to scale up information from single‐species laboratory studies to the population and community level.